Effect of Risedronate and Alendronate Treatment on Femoral Bone Quality and Collagen Integrity - Bagis, Selda; Comelekoglu, Ulku; Yalin, Serap; Yilmaz, Nejat; Ogenler, Oya; Yildiz, Altan; Nayci, Ali (Asian Journal of Chemistry, 2010)
The aim of this study was to investigate the effect of risedronate and alendronate treatment on bone biomechanical parameters and bone collagen integrity during postmenopausal osteoporosis. Sixty Sprague- Dawley female rats were divided into four groups: I, control (CON, n = 15); II, ovariectomized (OVX, n = 15); III, ovariectomized + alendronate (OVX-ALN, n = 15) and IV, ovariectomized + risedronate (OVX-RIS, n = 15). Ten weeks after ovariectomy, OVX-ALN rats were treated with alendronate sodium at the dose of 1.75 mg/kg body weight and OVXRIS rats received risedronate sodium at the dose of 0.5 mg/kg body weight using gavage twice per week for 12 weeks. Biomechanical measurements were performed at the femoral shaft and femoral neck of the left femur. In the OVX-ALN and OVX-RIS groups, strength, displacement, energy, strain and toughness were significantly increased when compared to OVX group. There were no significant differences between control and OVX-ALN and OVX-RIS groups for all biomechanical parameters at the femoral diaphysis and femoral neck. There were no statistically significant differences between the control, OVX, OVX-ALN and OVXRIS groups with respect to biochemical parameters. Normal collagen fiber organization was observed in control group, whereas the parallel packing of fibrils were completely replaced by a random arrangement in ovariectomized rats. However, OVX-ALN and OVX-RIS groups showed more regular arrangement than OVX group. In conclusion, the positive effect on bone biomechanical parameters and collagen integrity in ovariectomized rat femur was observed following the treatment of risedronate and alendronate.